Community Attitude to the Social Life of Mentally Retarded Teenager in Paninggilan Village - Alfiani Putri Awalia; Dedi Mulya; Yuni Tanjung Utami (Department of Special Education, 2022)
Attitude is a form of response that a person gives to something he sees. The purpose of this study was to find out how the community's attitude towards the social life of mentally retarded adolescents in Paninggilan Village. This research use qualitative descriptive approach. The respondents of this study were the community, which consisted of 10 people and 1 parent of a mentally retarded teenager. Data were collected through observations, interviews, documentation and field notes. The data analysis used was data reduction, data presentation and conclusion drawing. The results showed that the attitude of the community towards the social life of mentally retarded adolescents in Paninggilan Village could not be said to be completely good. When viewed based on the 3 components of the attitude acceptance aspect, the community already knows and understands a little what children with special needs are, the attitude given by the community to mentally retarded adolescents in Paninggilan Village is also good, but people still think that mentally retarded adolescents cannot be united with the community in general. Generally, when in an event because mental retardation can ruin an event, some of the community also still has an understanding that children with special needs (tunagrahita) are the same as ODGJ.